Como una luna en el agua - del Pino, Francisco (Revista Vórtex, 2014)
The title of the solo piano piece Como una luna en el agua, composed between June and July of 2014, refers to the end of the seventh chapter of the novel Rayuela (Hopscotch) by the Argentine writer Julio Cortázar, in which an allegorical description of a kiss takes the form of a prose poem.